Morphology description of early larval stages of the Asian horseshoe crab, Tachypleus gigas, and their exuviae - Zaleha, Kassim; Md Razak, Mohd Razali; Ahmad, Zuhairi; Ramli, Rohayu (Society of Cultural Studies and Social Sciences, 2023)
Knowledge of the growth and ecdysis or molting process in horseshoe crabs as a primitive member of arthropods is limited. This study aimed to investigate the development and ecdysis in the Asian horseshoe crabs through a Scanning Electron Microscope (SEM) approach. The fertilized eggs of Tachypleus gigas were collected from the natural breeding site at Kg. Johor Lama, Johor, and brought back to the laboratory for incubation and hatching. The molted exoskeletons (exuviae) from the first and second ecdysis were collected right away after each molting process, carefully dried and further processed and critical-point dried before coated with gold. The same preparation was made to examine the morphological feature for instars. They were then examined with the SEM. All prosomal appendages are in a complete form during the first instar stage as well as in the exuviae. The second instar stage is noted with the presence of the telson. The exuviae for the first (from instar 1), and then the second molt (from instar 2) showed consistently the suture opening located along the anterior edge of the prosoma at the exuviation suture. This suture is absent from the exoskeleton which is still intact with the larvae. There are notably two hinge pores located at both ends of the hinge which is the central dorsal part that joins the prosoma and opisthosoma. These pores are absent on the intact larvae’s exoskeleton. The findings contribute to further improving the understanding of early growth and ecdysis in this living fossil.